The Role of Self-Efficacy as a Mediating Variable between Discipline and Training on the Job Readiness of Participants in a Training Program in Japan - Ali Maskan; Marno Nugroho (Journal of Economics, Management, and Business, 2026)
Purpose – This study aims to examine and analyze the impact of training and discipline on the work readiness of participants in the vocational training program to Japan, positioning self-efficacy as a mediating variable. Methodology – This research adopts a quantitative approach using a survey method involving 123 individuals currently undergoing vocational education for the Japan program. Data analysis was performed using multiple linear regression and mediation analysis assisted by SPSS software. Findings – The research findings indicate that training and discipline have a positive and significant effect on self-efficacy. Furthermore, self-efficacy and discipline were proven to have a significant effect on work readiness, while training does not have a significant direct effect. Self-efficacy was identified as a crucial mediating factor in connecting the influence of training and discipline to the work readiness of participants. Implications – These results emphasize the importance of strengthening psychological aspects, specifically self-efficacy, in designing international job training programs to enhance participants' adaptation readiness in the Japanese work environment. Originality – This study contributes to human resource management literature by integrating discipline and training variables within a single self-efficacy mediation model specifically for the context of overseas job training participants.